(untitled) (Annals of Medical Research, 2021)
Aim: To compare of the affected eyes of the patients with unilateral herpetic keratitis with their fellow eyes and the healthy controls in terms of ocular surface parameters and corneal sensation.Materials and Methods: Both eyes of the consecutive patients with a PCR-proven diagnosis of unilateral chronic herpetic epithelial keratitis and the left eyes of age- and gender-matched healthy controls were included in the study. Schirmer’s test, tear break-up time (TBUT), corneal sensation, and tear osmolarity were investigated in all of the patients. Results: Forty-two eyes of 21 patients with unilateral herpetic keratitis and twenty-one eyes of 21 healthy controls who had no ocular pathology were included in the study. While the mean tear osmolarity of the eyes with herpetic keratitis was 317.3±15.6 mOsm/L, it was 313.2±16.1 mOsm/L for the fellow eyes, and 302.6±11.9 mOsm/L for the healthy eyes (p=0.002). Both herpetic eyes and fellow eyes had significantly higher tear osmolarity and lower TBUT values in comparison to the healthy controls (osmolarity: p=0.002 and p=0.03, and TBUT: p0.001 and p=0.021, respectively). While there was no significant difference between the fellow eyes and healthy eyes in terms of central and peripheral corneal sensation (p=0.4 and p=0.09, respectively), herpetic eyes had lower central and peripheral corneal sensation in comparison to the fellow eyes and healthy controls.Conclusion: This study showed that both the affected and fellow eyes of the patients with unilateral herpetic epithelial keratitis are affected in terms of dry eye without any significant loss in the corneal sensation of the fellow eye.